Effects of pulsed laser remelting on laser additively manufactured Al-50%Si alloy - Toh, Min Xiu (Nanyang Technological University, 2022)
Additive Manufacturing (AM) has been growing in popularity in recent years and directed energy deposition (DED) is an AM process that has been largely employed to fabricate materials with extremely complicated structures by depositing material layer by layer to build the final product. However, DED generates a great amount of residual stress on materials which worsens the overall properties of materials due to defects such as cracks and a rough surface finish. Thus, laser surface remelting (LSR) would be the focus in this project report to achieve refined microstructures that can lead to improved mechanical properties. Hypereutectic aluminium silicon (Al-Si) alloys have widespread applications in the automotive industry due to its good strength-to-weight ratio and low coefficient of thermal expansion, however, the growth of coarse primary silicon particles causes the material to become brittle which hinders its usage for various applications. Microstructure refinement can lead to a substantial improvement in the mechanical properties of hypereutectic Al-Si alloys, thus LSR is used on this material, specifically Al-50%Si alloy fabricated via DED in this experiment. The effects of LSR on the mechanical properties of Al-50%Si alloy are investigated in this report to optimise its laser processing parameters for enhanced properties that can be used extensively. Though this experiment, remarkable improvements have been observed after laser remelting with varying laser powers such as a substantial reduction in silicon particle size and improved microhardness with increasing laser power.